Alpha-1-antitrypsin bodies in the liver. Issue 2 (February 1977) - Blenkinsopp, W K; Haffenden, G P
Abstract : The cytoplasmic bodies in hepatocytes thought to indicate possession of the Z allele for alpha 1-antitrypsin deficiency were found in necropsy in 10 of 64 adults with cirrhosis, four of nine with hepatic fibrosis, and four of 15 with hepatocellular carcinoma. They were also found in six of 76 adults with severe panacinar emphysema, and in four of a control series of 110 adults with neither emphysema nor liver disease. The association of the bodies with each of the three liver diseases was statistically significant, but the association of the bodies with emphysema was not. It is considered probable that heterozygous (PiMZ) alpha 1-antitrypsin deficiency is associated with an increased incidence of cirrhosis, hepatic fibrosis, and hepatocellular carcinoma.